The Effect of Estrogen and Tamoxifen on Hepatocyte Proliferation in Vivo and in Vitro - Francavilla, Antonio (1989)
We have previously shown that changes in estrogen-hepatocyte interaction occur during liver regeneration. Following 70% hepatectomy, estrogen levels in the blood were elevated, the number of estrogen receptors in the liver was increased and there was an active translocation of estrogen receptors from the cytosol to the nucleus. The injection of tamoxifen, an estrogen antagonist, inhibits hepatocyte proliferation following partial hepatectomy. The administration of 1 μg tamoxifen per gm body weight at zero time or 6 hr after the operation resulted in a significant inhibition both of DNA synthesis and of the number of cells in mitosis. Injections of tamoxifen 12 hr or later after the operation had no effect. Concomitant injections of equimolar amounts of estrogen abolished the inhibition by tamoxifen. The effects of estrogen and tamoxifen were also tested on hepatocytes in primary culture. Estrogens in the presence of 5% normal rat serum stimulated hepatocyte DNA synthesis as determined by [(3)H]thymidine incorporation and the labeling index, whereas epidermal growth factor-induced DNA synthesis in the absence of normal rat serum was strongly inhibited. Tamoxifen, in contrast, inhibited DNA synthesis of hepatocytes in the presence of 5% normal rat serum and reversed the stimulatory effect of estrogen in the same system. Attempts to elucidate the mechanism of tamoxifen inhibition in vitro indicated that one effect of tamoxifen is to prevent the amiloride-sensitive Na(+) influx necessary to initiate hepatocyte proliferation.